Chemical investigation of the leaf and rhizome essential oils of Zingiber zerumbet (L.) Smith from Bangladesh - Mohammad Nazrul Islam Bhuiyan; Jasim Uddin Chowdhury; Jaripa Begum (Bangladesh Pharmacological Society, 2008)
Zingiber zerumbet (L.) Smith leaf and rhizome oils, obtained by hydrodistillation, were analyzed by gas chromatography mass spectroscopy (GC-MS). Twenty-nine components were identified in the leaf oil. The major components were zerumbone (36.98%); a-caryophyllene (16.35%) and camphene (9.24%). Thirty components were identified in rhizome oil with the main components being in zerumbone (46.83%); a-caryophyllene (19.00%) and 1,5,5,8-tetramethyl-12-oxabicyclo[9.1.0]dodeca-3,7-dieneÂ  (4.28%). The compositions of both oils varied qualitatively and quantitatively.